2023
DOI: 10.1148/radiol.221795
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Variants Infection in Relationship to Imaging-based Pneumonia and Clinical Outcomes

Abstract: Background Few reports have evaluated the effect of the SARS-CoV-2 variant and vaccination on the clinical and imaging features of COVID-19. Purpose To evaluate and compare the effect of vaccination and variant prevalence on the clinical and imaging features of infections by the SARS-CoV-2. Materials and Methods Consecutive adults hospitalized for confirmed COVID-19 at three centers (two academic medical centers and one community hospital) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…On the contrary, Crombé et al found no significant difference in vaccine effectiveness against severe CT pneumonia between the Omicron-predominant and Delta-predominant phases. This result is similar to the findings of Lee et al ( 7 ). Furthermore, vaccine effectiveness did not wane in terms of typical CT findings and the severity of COVID-19 pneumonia.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…On the contrary, Crombé et al found no significant difference in vaccine effectiveness against severe CT pneumonia between the Omicron-predominant and Delta-predominant phases. This result is similar to the findings of Lee et al ( 7 ). Furthermore, vaccine effectiveness did not wane in terms of typical CT findings and the severity of COVID-19 pneumonia.…”
supporting
confidence: 93%
“…Therefore, it is important to assess the impact of vaccination and Omicron on CT manifestations separately. To date, one retrospective study ( 7 ) has examined whether vaccination and Omicron were independently associated with less severe disease. In that study, multivariable analysis showed that although Omicron reduced the risk of severe CT pneumonia (odds ratio [OR], 0.7), vaccination provided an even more significant reduction (ORs, 0.11 for full vaccination and 0.05 for booster vaccination).…”
mentioning
confidence: 99%
“…In 2180 hospitalized patients with COVID-19, CT was more likely to be negative for pneumonia during periods of Omicron versus Delta variant prevalence (71% vs 35%, respectively; P < .001), and the Omicron variant had a lower risk of CT pneumonia severity (odds ratio, 0.71; P = .04) and clinical severity (odds ratio, 0.43; P = .004) than the Delta variant ( 67 ) ( Fig 6 ). The proportion of patients with an atypical CT pattern was higher in the Omicron variant group than in the Delta variant group ( 67 , 68 ) ( Table 2 ) ( Fig 6D ).…”
Section: Special Considerationsmentioning
confidence: 99%
“…Infection with the Omicron variant is characterized by upper respiratory symptoms such as rhinorrhea, sore throat, sneezing, and hoarse voice, while the absence of anosmia may reflect reduced tropism toward extra-respiratory tissues [37]. Moreover, the Omicron variant has been found to be less likely to cause severe pneumonia than the Delta variant even after adjustment for vaccination status in a multivariable analysis [38]. In patients infected with the Omicron variant, pneumonia was more strongly associated with old age, male gender, and diabetes than in patients infected with previous variants [39].…”
Section: From the Lungs To The Nosementioning
confidence: 99%